Difficulties in differential diagnosis of alopecia in the practice of dermatologists: Clinical cases - P. S. Osmolovskaya; N. L. Sycheva; F. A. Psavok (Кубанский научный медицинский вестник, 2024)
Background. All types of alopecia fall into two main categories: scarring and non-scarring alopecias. Among these, certain types frequently pose challenges in differential diagnosis due to their similar clinical manifestations, thus necessitating specific examinations to be made for confirmation of the diagnosis. For instance, trichotillomania may be easily confused with alopecia areata. Description of clinical cases. The paper presents three clinical observations of patients with both scarring and non-scarring alopecia and highlights the challenges in establishing a definitive diagnosis due to the similarities in clinical presentations. The study emphasized the importance of thorough examination and close attention to patients with long-standing areas of hair thinning, along with the necessity for meticulous differential diagnostic efforts. In addition, the significance of pathological examination is considered as an indispensable tool for the evaluation of most similar cases of scarring and non-scarring alopecias. Conclusion. Early verification of the diagnosis and timely initiation of therapy for hair disorders appear crucial, both for the potential restoration of hair growth and for the prevention of further hair loss.